Exploring the rhizospheric bacterial community of selected millets for plant growth promotion activity in tomato - Sakthivel, Anitha; Santhanalakshmi, Balasubramanian; Sahayarayan, Jesudass Joseph; Sivanandhan, Ganeshan; Mani, Ravishankar Ram; Chang, Soon Woong; Ravindran, Balasubramani; Chokkakula, Santosh; Kapildev, Gnanajothi (Frontiers in Plant Science, 2025)
Millets are highly nutritious crops mostly cultivated in xeric regions of Asia and Africa. The specific agro-climatic characteristics of millets enable the rhizosphere to host diverse microorganisms that assist in the crop’s progression under harsh weather conditions. This research work intends to evaluate the plant growth-promoting (PGP) potential of the rhizospheric microbes isolated from the soil of Panicum sumatrense and Eleusine coracana from Kunnanchala and Varagampadi, residing areas of Irulas Tribal Community located in the Attapadi Hills of Kerala and Tamil Nadu, respectively. A total of 53 bacterial isolates with unique colony morphology were initially subjected to the nitrogen fixation test. Twenty-six isolates that demonstrated positive results for nitrogen fixation were characterized for phosphate solubilization, ammonia, indole acetic acid (IAA), siderophore, hydrogen cyanide (HCN), and hydrolytic enzyme production, molecular characterization, and antagonistic activity against the common plant pathogens Fusarium oxysporum and Colletotrichum gloeosporioides. The principal component analysis revealed that SA1 (Staphylococcus gallinarum) and MS6 (Kosakonia sacchari) exhibited the highest values for IAA production (0.37 ± 0.015 mg/mL) and PSI (3.36 ± 0.03), respectively. MS3 (Bacillus velezensis) demonstrated the most promising results in antagonism (91.32 ± 0.57) and ammonia production (0.11 ± 0.020 mg/mL). All the bacterial isolates exhibited a notable improvement in germination, shoot length, root length, and vigor index of Solanum lycopersicum. The most prominent results in germination studies were noted in K. sacchari (MS6), with the most pronounced effects, including a 100% germination rate, 2.58 ± 0.01 cm of shoot length, 7.61 ± 0.03 cm of root length, and a vigor index of 1019. The results of the invitro PGP traits are sufficient to support future tests on the promotion of growth invivo for these seven strains in a single or consortium.